Effects of in vitro digestion and fermentation of Nostoc commune Vauch. polysaccharides on properties and gut microbiota. (1st April 2022) - Li, Hailong; Liu, Su; Liu, Yue; Li, Weinan; Niu, Aijing; Ren, Ping; Liu, Yingying; Jiang, Chengshuang; Inam, Muhammad; Guan, Lili
Abstract: Nostoc commune Vauch. polysaccharides (NCVP) was extracted from Nostoc commune Vauch. with strong biological properties. The molecular weight of NCVPs (NCVP, NCVP-S, NCVP-G, and NCVP-I) exhibited a downward trend, and the molar ratio of constituent monosaccharides of NCVPs significantly changed, implying that NCVP could be degraded under in vitro simulated digestion. The antioxidant activities of NCVPs were significantly improved during in vitro digestion. In addition, NCVPs had a prebiotic effect on Lactobacillus strain. During in vitro fermentation, NCVP was degraded and utilized by the gut microbiota, and a variety of short-chain fatty acids (SCFAs) were formed. Functional gene prediction of 16S rDNA sequencing data inferred that NCVP could promote gut metabolism and improve the body's defense mechanism. Overall, these findings emphasized that NCVP is beneficial by maintaining the gut health and can be used as potential prebiotics in the functional foods and medicine industries. Graphical abstract: Unlabelled Image Highlights: In vitro digestion of Nostoc commune Vauch. polysaccharides (NCVP) was studied. Physicochemical properties and biological activity of NCVP significantly changed during gastrointestinal digestion. NCVP was degraded and utilized by gut microbiota. The acetic acid, propionic acid and i-butyric acid were on the rise with fermentation time. NCVP can promote beneficial gut microbiota including Firmicutes and Bacteroidetes .